BSCI-20 STING EPIGENETIC SILENCING IN GLIOMAS CAN BE RESCUED BY METHYLTRANSFERASE INHIBITION: IMPLICATIONS FOR NOVEL THERAPEUTIC APPROACHES. (5th August 2022) - Low, Justin; Chandramohan, Vidya; Bowie, Michelle; Brown, Michael; Waitkus, Matthew; Briley, Aaron; Stevenson, Kevin; Fuller, Rebecca; Hostettler, Janell; Reitman, Zachary; Charbonneau, Casey; Keir, Stephen; et al.
Abstract: The stimulator of interferon genes (STING) is a key component of the innate immune response to pathogenic cytosolic DNA, resulting in IRF3- and NFκB-dependent transcription of type I interferons (IFN) and pro-inflammatory cytokines. STING activation primes endogenous antitumor immunity and is disrupted in a variety of cancers. Here we investigate STING signalling in glioblastoma (GBM) patient samples. STING agonist treatment of ex vivo gliomas leads to inconsistent induction of type I IFN responses that are restricted to tumor associated myeloid cells. Indeed, single-cell transcriptome and multiplex immunofluorescence analyses demonstrate that STING expression is suppressed in neoplastic cells but not tumor-associated immune cells or stroma. Methylation analyses reveal a STING promoter region that is highly methylated in bulk tumor samples from glioma and other neuroectoderm-derived cancers, but not in most extracranial cancers. Methylation in this region strongly correlates inversely with STING RNA expression. STING epigenetic silencing is also present in normal fetal and adult brains. We demonstrate that STING expression in glioma cell lines may be rescued by decitabine, a DNA methyltransferase inhibitor (DNMTi) that is commonly used to treat hematologic malignancies. However, transduction of a STING-expressing vector into these glioma cell lines is insufficient to reconstitute STING signalling, suggesting that additional decitabine-stimulated mechanisms are necessary for STING pathway rescue. Collectively, our results suggest that epigenetic silencing of STING occurs early in brain development and may provide an immunosuppressive context for the genesis of brain tumors. Furthermore, our work raises the potential of epigenetic modulation to reconstitute STING signalling as a therapeutic strategy for glioblastoma and potentially other STING-silenced, immunologically-cold cancers.